Impact of SARS-CoV-2 vaccines and recent chemotherapy on COVID-19 morbidity and mortality in patients with soft tissue sarcoma: an analysis from the OnCovid registry - Bruno Vincenzi; Alessio Cortellini; Alessandro Mazzocca; Sarah Orlando; Davide Romandini; Juan Aguilar-Company; Isabel Ruiz-Camps; Claudia Valverde Morales; Simeon Eremiev-Eremiev; Carlo Tondini; Joan Brunet; Rossella Bertulli; et al. (Therapeutic Advances in Medical Oncology, 2024)
Background: To date, limited evidence exists on the impact of COVID-19 in patients with soft tissue sarcoma (STS), nor about the impact of SARS-CoV-2 vaccines and recent chemotherapy on COVID-19 morbidity and mortality in this specific population. Methods: We described COVID-19 morbidity and mortality among patients with STS across ‘Omicron’ (15 December 2021–31 January 2022), ‘Pre-vaccination’ (27 February 2020–30 November 2020), and ‘Alpha-Delta’ phase (01 December 2020–14 December 2021) using OnCovid registry participants (NCT04393974). Case fatality rate at 28 days (CFR 28 ) and COVID-19 severity were also described according to the SARS-CoV-2 vaccination status, while the impact of the receipt of cytotoxic chemotherapy within 4 weeks prior to COVID-19 on clinical outcomes was assessed with Inverse Probability of Treatment Weighting (IPTW) models adjusted for possible confounders. Results: Out of 3820 patients, 97 patients with STS were included. The median age at COVID-19 diagnosis was 56 years (range: 18–92), with 65 patients (67%) aged < 65 years and most patients had a low comorbidity burden (65, 67.0%). The most frequent primary tumor sites were the abdomen (56.7%) and the gynecological tract (12.4%). In total, 36 (37.1%) patients were on cytotoxic chemotherapy within 4 weeks prior to COVID-19. The overall CFR 28 was 25.8%, with 38% oxygen therapy requirement, 34% rate of complications, and 32.3% of hospitalizations due to COVID-19. CFR 28 (29.5%, 21.4%, and 12.5%) and all indicators of COVID-19 severity demonstrated a trend toward a numerical improvement across the pandemic phases. Similarly, vaccinated patients demonstrated numerically improved CFR 28 (16.7% versus 27.7%) and COVID-19 morbidity compared with unvaccinated patients. Patients who were on chemotherapy experienced comparable CFR 28 (19.4% versus 26.0%, p = 0.4803), hospitalizations (50.0% versus 44.4%, p = 0.6883), complication rates (30.6% versus 34.0%, p = 0.7381), and oxygen therapy requirement (28.1% versus 40.0%, p = 0.2755) compared to those who were not on anticancer therapy at COVID-19, findings further confirmed by the IPTW-fitted multivariable analysis. Conclusion: In this study, we demonstrate an improvement in COVID-19 outcomes in patients with STS over time. Recent exposure to chemotherapy does not impact COVID-19 morbidity and mortality and SARS-CoV-2 vaccination confers protection against adverse outcomes from COVID-19 in this patient population.